Perbandingan Kadar High Density Lipoprotein dan Indeks Massa Tubuh antara Akseptor KB Pil Kombinasi dengan Depo Medroksiprogesteron - Sitinjak, Helti Lestari; Rita, Rauza Sukma; ., Yusrawati . (Media Kesehatan Masyarakat Indonesia, 2019)
More than six million women worldwide use contraceptive injection and the popular contraceptive method used is contraceptive pill. This is due to one of the side effects of combination pill contraception is to increase triglyceride levels, total cholesterol and changes in carbohydrate metabolism while the side effects of Depot Medroxyprogesterone Acetate are irregular menstruation/amenorrhea, changes in body weight and lipid changes. This research is an observational with cross sectional comparative approach to 36 combination pill acceptor and 36 Depot Medroxyprogesterone Acetate acceptor. This study was conducted ini the area of Andalas and Lubuk Buaya Health Center. The sampling method used in this research was simple random sampling method. The analysis was used T-Independent test and chi square test. The results showed that High Density Lipoprotein leves Depot Medroxyprogesterone Acetate (63,97±12,75 mg/dl) vs combined contraceptive pill (60,06±15,57 mg/ dl), p=0,25 and Body Mass Index levels of overweight combined contraceptive pill acceptor higher than Depot Medroxyprogesterone Acetate (p=0,08). Results of this study concluded was that there were no significant differences in the levels of High Density Lipoprotein and Body Mass Index between combined contraceptive pill and Depot Medroxyprogesterone Acetate acceptor